THE ROLE OF CAMEL RATIONS AS AN EARLY WARNING SYSTEM FOR FINANCIAL DISTRESS THROUGH A BENCHMARKING APPOROACH: A PERFORMANCE ANALYSIS OF BANK BTN COMPARED TO STATE-OWNED BANKS IN INDONESIA - Randy Rauf; A. Alya Aurelya Bachtiar; Nur Khaerunnisa Zakir; Asri Usman; Alimuddin (RADJA PUBLIKA, 2026)
This study aims to analyze the role of the CAMEL ratio as an early warning system in detecting potential financial distress at Bank Tabungan Negara through a benchmarking approach with other state-owned banks in Indonesia. The study employed a quantitative approach using descriptive and comparative methods. Secondary data were obtained from annual reports and financial statements of state-owned banks during the 2015–2024 period. The research samples consisted of Bank Tabungan Negara, Bank Rakyat Indonesia, Bank Mandiri, and Bank Negara Indonesia. The analysis used CAMEL ratios, namely Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Operating Expenses to Operating Income (BOPO), Return on Assets (ROA), and Loan to Deposit Ratio (LDR). The results show that all state-owned banks are generally categorized as healthy because they maintain CAR above the minimum regulatory standard and NPL below the maximum threshold. However, Bank Tabungan Negara demonstrated relatively weaker performance compared to other state-owned banks, particularly in terms of asset quality, profitability, and liquidity. BTN recorded the highest NPL ratio of 3.43%, the lowest ROA of 0.78%, and the highest LDR of 102.20%, indicating higher credit risk, lower profitability, and greater liquidity pressure. The study also found that the CAMEL ratio is effective as an early warning system in detecting potential financial distress. The most dominant indicators signaling financial distress were NPL, ROA, and LDR. In addition, Bank Rakyat Indonesia showed the most stable financial performance among state-owned banks during the research period.